Gender-based differences in cognitive needs of Iranian rural health workers to perform osteoporosis prevention educational programs: an application of health belief model. Issue 4 (4th July 2021) - Nadrian, Haidar; Nejati, Ahmad; Latifi, Arman; Aghemiri, Mehran; Hajizadeh, Hossein; Mahmoodi, Hassan; Shirzadi, Shayesteh; Heizomi, Haleh
ABSTRACT: Rural health workers play a detrimental role in implementing rural osteoporosis prevention programs. To successfully implement such programs, addressing their gender-based cognitive needs seems to be necessary. Our aim in the present study was to investigate gender-based differences in determinants of educating rural communities on osteoporosis prevention among Iranian rural health workers (RHWs) applying the health belief model (HBM). In this cross-sectional study, conducted in 2017, 280 RHWs were recruited to participate in the study, through random sampling. An HBM-based researcher-made questionnaire was developed to collect data. Face, content, construct and convergent validity and reliability of the scales were approved. After splitting data by gender, hierarchical linear regression was used to investigate the predictors of RHWs' performance on osteoporosis prevention education programs (OPEPs). In Confirmatory Factor Analysis (CFA), the measurement model was found to be with a good fit to the data in the assumed model (χ2 [466] = 999.466, p < 0.001, CFI = 0.921, NFI = 0.821, TLI = 0.913, RMSEA = 0.048[0.043–0.054]). Among male RHWs, perceived barriers (p < 0.01), knowledge (p < 0.05) and the mean distance of health house from the marginal villages (p < 0.05) were significant predictors of the RHWs' performance on OPEPs (cumulative adjusted R 2 = 0.790). Among female RHWs, perceived barriers (p < 0.01), self-efficacy (p < 0.05) and cues to action (p < 0.05) were significant predictors of the outcome variable (cumulative adjusted R 2 = 0.404). The findings of the present study are informative for the development of targeted interventions aimed at fostering RHWs' performance on OPEPs.